PHARMACOGNOSTIC PROFILE AND PHARMACOLOGAL ACTIVITIES OF Eleutherine plicata - Zandonadi Meneguelli, Alexandre; Fernanda Buccini, Danielli; Cardoso Roriz , Beatriz; Eduardo Saranz Camargo , Ely; Elisa Moreno , Susana (South American Journal of Basic Education, Technical and Technological, 2021)
Eleutrherine plicata is a medicinal plant which is characterized by presenting clinical evidence and therapeutic uses, biological activities, including antibacterial, antifungal, antioxidant, anti-inflammatory and analgesic effects. The purpose of this article is for pharmacognostic studies to identify chemical components, evaluate the cytotoxic, antimicrobial and anti-inflammatory potential of chloroform and methanolic extracts of Eleutrherine plicata. The extracts were produced using the E.e plicata bulb with hexane and methanol solvents according to the Brazilian Pharmacopoeia. In identification of secondary metabolites, colorimetric methods were used. The extracts were subjected to tests in vitro and in vivo. In cytotoxic assay, hemolysis was determined using concentrations of 150 to 2.34 µg / mL-1. In anti-tumor test, to determine the cytotoxicity of extracts, Ehrlich’s ascitic tumor cells were used (ETA). Cell viability was determined by the colorimetric method of MTT in 24 and 48 hours, using serial dilution of 1024 to 1 µg /mL-1 .Antibacterial activity was assessed using the disk diffusion methodology, in serial dilution of 1024 to 16 µg / mL-1. The anti-inflammatory activity was evaluated by neutrophil migration method and tested at concentrations of 1; 5 e 15 mg / kg-1. Pharmacognostic tests showed the presence of tannins, anthraquinone glycosides and flavonid glycosides. In the cytotoxic assay, hemolysis was observed at concentrations of 150 to 75µg / mL-1. ETA Test, in both extracts; showed a reduction in viability at the highest concentrations tested, at both times analyzed. Antimicrobial activity showed significant inhibition in methanolic extract on E.coli in concentrations of 1024 to 16 µg / mL-1. There was not anti-inflammatory activity for the tested concentrations of both extracts methanolic and hexanic. Both extracts showed a 70% reduction in cell viability in the cytotoxic assay. Since this trial was conducted with tumor cells, it arouses interest in antitumor investigation, which is a promising result; among the tests performed.